Late Metastases from a Thin Primary Cutaneous Malignant Melanoma - Regina Caldas; Filipa T. Almeida; Teresa Pereira; Inês Carvalho; Sofia D. Carvalho; Celeste Brito (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Cutaneous malignant melanoma is the third most common type of skin cancer, and its incidence has been rising. Its mortality rate is considerable, due to an aggressive phenotype and great ability of dissemination, mainly in the first years of follow- -up. Late recurrences, those presenting more than 10 years after diagnosis, are rare. The main prognostic factor of cutaneous malignant melanoma is tumor thickness, which also guides management. Thin tumors often have a good prognosis. We report a case of a 66-year-old woman with a history of excision of a thin primary cutaneous malignant melanoma of the dorsum, presenting 16 years later with an unexpected, rapidly progressing and lethal recurrence.